Pencegahan Plagiarisme Dalam Pembelajaran Pendidikan Agama Kristen Secara Daring di SMA Negeri 9 Manado - Febri Manoppo; Firmanians Tuerah (Jurnal Ilmiah Wahana Pendidikan, 2022)
The purpose of this study was to describe the understanding of Christian students about plagiarism, the forms of plagiarism and the causes, as well as the efforts of Christian Religious Education teachers in preventing plagiarism in online learning of Christian Religious Education at SMA Negeri 9 Manado. This study used a qualitative method with a descriptive method which was carried out at SMA Negeri 9 Manado in 2021. Data were collected through observation, interviews and documentation techniques. Researchers collected data on data sources, namely 2 Christian Religious Education teachers and 8 Christian students. The research time starts from November 2020 to July 2021. From the results of data analysis and interpretation, it is indicated that: (1) Christian students' understanding of plagiarism is good, but the forms and types of plagiarism are not well understood, so they need to be sharpened. (2) The forms of plagiarism carried out in online learning of Christian Religious Education at SMA Negeri 9 Manado are plagiarism from the internet, from material books and from fellow students. (3) The factors that cause plagiarism are freedom to access the internet, increased feelings of boredom and laziness, poor networks, and the number of assignments that students receive from teachers during online learning. (4) The efforts made by Christian Religious Education teachers are to motivate and encourage students, as well as make learning videos so that students who have difficulty participating in online learning in real time can access learning videos at any time so that plagiarism can be minimized.